Chemical reactor analysis and applications for the practicing engineer - Theodore, Louis (Essential engineering calculations series., 2012)
This books format follows an applications-oriented text and serves as a training tool for individuals in education and industry involved directly, or indirectly, with chemical reactors. It addresses both technical and calculational problems in this field. While this text can be complimented with texts on chemical kinetics and/or reactor design, it also stands alone as a self-teaching aid. The first part serves as an introduction to the subject title and contains chapters dealing with history, process variables, basic operations, kinetic principles, and conversion variables. The second part.